2014
DOI: 10.1155/2014/563243
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Characteristics Influencing the Development of Gestational Diabetes in Obese Women Receiving 17-alpha-Hydroxyprogesterone Caproate

Abstract: Objective. Gestational diabetes (GDM) and obesity portend a high risk for subsequent type 2 diabetes. We examined maternal factors influencing the development of gestational diabetes (GDM) in obese women receiving 17-alpha-hydroxyprogesterone caproate (17OHPC) for preterm delivery prevention. Materials and Methods. Retrospectively identified were 899 singleton pregnancies with maternal prepregnancy body mass indices of ≥30 kg/m2 enrolled for either 17OHPC weekly administration (study group) or daily uterine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“… SGA small for gestational age: <10th percentile, AGA appropriate for gestational age: 10th–90th percentile, LGA large for gestational age: >90th percentile, Macrosomia Estimated fetal weight ≥ 4 kg [ 25 ] a Missing data are excluded from statistical analyses b Chi-square test or Fisher’s exact test for categorical variables and Wilcoxon rank sum test for continuous variables c Univariate logistic regression …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… SGA small for gestational age: <10th percentile, AGA appropriate for gestational age: 10th–90th percentile, LGA large for gestational age: >90th percentile, Macrosomia Estimated fetal weight ≥ 4 kg [ 25 ] a Missing data are excluded from statistical analyses b Chi-square test or Fisher’s exact test for categorical variables and Wilcoxon rank sum test for continuous variables c Univariate logistic regression …”
Section: Resultsmentioning
confidence: 99%
“…SGA small for gestational age: <10th percentile, AGA appropriate for gestational age: 10th–90th percentile, LGA large for gestational age: >90th percentile, Macrosomia Estimated fetal weight ≥ 4 kg [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the diabetogenic effect of progesterone supplementation have yielded inconclusive results. A number of studies have suggested that intramuscular administration of 17-alpha hydroxyprogesterone caproate (17 OHP-C) might pose a risk of increasing the incidence of GDM [ 8 , 11 13 ]. On the other hand, a secondary analysis of two randomized placebo-controlled trials of 17 OHP-C found no association with higher rates of GDM in either group [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the diabetogenic effects of progesterone supplementation have been investigated in in vitro [ 9 , 10 ] as well as in retrospective [ 8 , 11 , 12 ] and prospective [ 13 – 15 ] studies, the results remain inconclusive. Women with an increased risk for preterm delivery due to shortened cervical length with a transvaginal ultrasound scan carried out between 16 + 0 and 24 + 0 weeks of pregnancy showing a cervical length of < 25 mm and/or history of a previous preterm birth in our department routinely receive vaginal progesterone treatment starting at 16–20 weeks of gestation until 36 weeks of gestation in an attempt to prolong pregnancy.…”
Section: Introductionmentioning
confidence: 99%